Comparative Study on Racial Inequality in Higher Education in Brazil and South Africa - Souza, Eugenio Gabriela Fernanda (Department of Social Development, 2024)
This research investigated how racial aspects impacted on access to higher education in Brazil and South Africa, respectively. It also tried to determine how race influenced the completion of higher education in both countries. Based on a descriptive quantitative research design, the researcher retrieved data on enrolment and graduation in higher education from the Department of Higher Education and Training (DHET) in South Africa and Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira of Brazil (INEP in Portuguese) and then filtered it using population groups. Each country was assessed individually to identify the panorama of higher education in terms of racial distribution of students. Then similarities and differences were identified, considering both countries' social formation and the structure of their education systems. The findings of the study were able to uncover the importance of affirmative action policies to tackle racial and social inequalities in higher education in both countries. In Brazil, the findings showed that a total number of vacancies in higher education had a significant expansion during the period of the study. However, the findings revealed that the total number of white students who had enrolled in institutions of higher education and had graduated was greater than the total number of black students, during the period of the research study. In addition, there was a tendency for this gap to decrease over time. The study identified a variation related to the reduction of the gap for graduating black and white students. It seemed slower than the reduction in the gap for enrolment, but both indicators have been improving regarding racial inequalities. The study discovered that higher education system in Brazil had introduced new tools to promote access to education and reduce the dropout rate. Programmes such as the quota system, ProUni, Fies, Sisu and permanence policies were identified as being responsible for improving the indicators of racial equality in higher education in the period of study. In the case of South Africa, the study was able to determine that the total number of students enrolled in and graduating from higher education had increased in the period studied. On the one hand, black African students represented the majority of students enrolled in and had graduated from higher education throughout the whole assessed period. However, the proportion of black African students in higher education was still not equivalent to their weight in the population as a whole. On the other hand, the reality for white students was the opposite. During the interval studied, the proportion of white students in higher education outweighed their participation in the general population. Such differences have been reducing over time, suggesting a slight reduction in racial inequality in higher education South Africa. The study also revealed that racial aspects impacted access to and the completion of higher education in both Brazil and South Africa. The study concluded with policy recommendations. A key recommendation of the study was for the development of policies that would tackle the challenge of dropouts which the study identified as a major issue for the higher education in both countries.